Language, morality, and modern Islam: A linguistic reframing of ethical challenges in Islamic thought - Nesher, Elinor (Association for Scientific Computing Electrical and Engineering (ASCEE), 2025)
This study argues for an urgent reform in Islamic thought, positing that its capacity to address modern challenges is intrinsically linked to the evolution of its religious language. While Sharia is considered eternal, its application requires continuous dynamic interpretation (ijtihad), a process that is fundamentally discursive. This research employs a textual-historical and linguistic-pragmatic analysis to investigate how religious authority, ethical values, and moral norms are constructed, maintained, and contested through language. It examines the linguistic mechanisms such as speech acts, modal verbs, and evaluative language that underpin religious discourse and explores how semantic shifts and innovations respond to issues of globalization, science, and pluralism. The paper concludes by proposing an adaptive ethical-linguistic framework that harmonizes tradition with contemporary innovation, balancing individual moral responsibility with collective Islamic values.